Comparison of serum amyloid A protein and C-reactive protein levels as inflammatory markers in periodontitis (2015)
ABSTRACT: Purpose: The purpose of this study was to compare serum amyloid A (SAA) protein levels with high-sensitive C-reactive protein (hs-CRP) levels as markers of systemic inflammation in patients with chronic periodontitis. The association of serum titers of antibodies to peri- Odontal microbiota and SAA/hs-CRP levels in periodontitis patients were also studied. Methods: A total of 110 individuals were included in this study. Patients were assessed for levels of hs-CRP and SAA. Nonfasting blood samples were collected from participants at the time of clinical examination. The diagnosis of adipose tissue disorders was made according to previously defined criteria. To determine SAA levels, a sandwich enzyme-linked immunosorbent assay was utilized. Paper points were transferred to a sterile tube to obtain a pool of samples for polymerase chain reaction processing and the identification of Porphyromonas gingivalis, Aggregatibacter actinomycetemcomitans, and Tannerella forsythia. The serum level of IgG1 and IgG2 antibodies to P. gingivalis, A. actinomycetemcomitans, and T. forsythia was also determined. Results: SAA and hs-CRP levels were higher in periodontitis patients than in controls (P<0.05). In bivariate analysis, high levels of hs-CRP (>3 mg/L) and SAA (>10 mg/L) were significantly associated with chronic periodontitis (P=0.004). The Spearman correlation analysis between acute-phase proteins showed that SAA positively correlated with hs-CRP (r=0.218, P=0.02). In the adjusted model, chronic periodontitis was associated with high levels of SAA (odds ratio [OR], 5.5; 95% confidence interval [CI], 1.6–18.2; P=0.005) and elevated hs-CRP levels (OR, 6.1, 95% CI, 1.6–23.6; P=0.008). Increased levels of serum IgG2 antibodies to P. gingivalis were associated with high levels of SAA (OR, 3.6; 95% CI, 1.4–8.5; P=0.005) and high concentrations of hs-CRP (OR, 4.3; 95% CI, 1.9–9.8; P<0.001). Conclusions: SAA and hs-CRP concentrations in patients with chronic periodontitis are comparably elevated. High serum titers of antibodies to P. gingivalis and the presence of periodontal disease are independently related to high SAA and hs-CRP levels.